2017
DOI: 10.1002/cbdv.201600331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Predominant Phytochemical Compounds and Cytotoxic Activity of Wild Olive Leaves (Olea europaea L. ssp. sylvestris) Harvested in South Portugal

Abstract: This study has been aimed at providing a qualitative and quantitative evaluation of selected phytochemicals such as phenolic acids, flavonoids, oleuropein, fatty acids profile, and volatile oil compounds, present in wild olive leaves harvested in Portugal, as well as at determining their antioxidant and cytotoxic potential against human melanoma HTB-140 and WM793, prostate cancer DU-145 and PC-3, hepatocellular carcinoma Hep G2 cell lines, as well as normal human skin fibroblasts BJ and prostate epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
5
19
0
2
Order By: Relevance
“…Melnyk et al 46 identified rutin as the highest content of phenolics in the rue methanolic extract, consistent with the present work. Several studies 48 , 49 have reported oleuropein and its derivatives as the dominant phenolics in the olive leaf, according with our results. As shown in data (Table 2 and Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Melnyk et al 46 identified rutin as the highest content of phenolics in the rue methanolic extract, consistent with the present work. Several studies 48 , 49 have reported oleuropein and its derivatives as the dominant phenolics in the olive leaf, according with our results. As shown in data (Table 2 and Fig.…”
Section: Resultssupporting
confidence: 90%
“…In some cases, phenylethanoids, which are phenethyl alcohol-structured phenolic antioxidants, were abundantly found in olive leaves, including oleuropein and its derivatives, followed by tyrosol and verbascoside. These molecules may conduct to its high antioxidant properties 11 , 49 . Tyrosol existed in highest concentration in rosemary (4.56 mg g −1 ), but in small quantity in olive leaf (0.75 mg g −1 ) and rue (0.19 mg g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The other two molecules, luteolin (from traces to a maximum of 3 g/kg −1 DW) and verbascoside, were detected at low levels in all the cultivars examined, in accordance with the literature [4,26]. Verbascoside is a hydroxycinnamic derivative typical of olive fruit and it has been found in small amounts in olive leaves, as reported by Makowska-Wazs et al [40] for wild olive trees and by Pereira et al [41] for the Portuguese olive cultivar Cobrançosa.…”
Section: Resultssupporting
confidence: 90%
“…Flavonoid and phenolic acid analysis was performed according to Makowska‐Wąs et al ., using a Dionex HPLC system with a PDA 100 UV–visible detector Hypersil Gold (C‐18) column (5 µm, 250 × 4.6 mm, Thermo EC) mobile phase of 1% formic acid in water (A) and acetonitrile (B) in a gradient mode 5–60% B over 60 min, at a flow rate of 1 mL min −1 . Identification of the compounds was conducted by comparing their retention times and UV spectrum with those of the standards (phenolic acids: caffeic, chlorogenic, gentisic, sinapic and ferulic; and flavonoids: isoquercitrin, robinin, morin, myricetin, apigenin, kaempferol and quercetin were used; 10 mg of each standard was dissolved in 10 mL HPLC‐purity methanol to obtain 1 mg mL −1 stock solution).…”
Section: Methodsmentioning
confidence: 99%